Introduction and ex-situ conservation of red-list medicinal plants in Andhra University Campus - Rao, J Prakasa; Padal, SB (International Journal of Environment, 2016)
Medicinal plants are now under great pressure due to their excessive collection so there is a need to immediate attention for conservation of some important medicinal and red list plants. During the period of 2009-2015 germplasm was collected and introduced in to the Andhra University Botanical Garden. A total of 72 introduced species belonging to 66 genera and 35 families were successfully acclimatized in the botanical garden, included 18 red list plants. After acclimatization all plants are transferred to the garden and special block was maintaining as red list medicinal garden. International Journal of Environment Vol.5(3) 2016, pp.31-42